Study of crystal-field excitations and infrared active phonons in TbMnO3. (3rd April 2018) - Mansouri, S; Jandl, S; Balli, M; Fournier, P; Mukhin, A A; Ivanov, V Yu; Balbashov, A; Orlita, M
Abstract: The Tb 3+ ( 4f 8 ) crystal-field (CF) excitations and the infrared phonons in TbMnO3 are studied as a function of temperature and under an applied magnetic field. The phonon energy shifts reflect local displacement of the oxygen ions that contribute to the CF energy level shifts below 120 K and under magnetic field. The CF polarized transmission spectra provide interesting information about the debated nature of the excitations at 41, 65, 130 cm −1 . We also evaluate the contribution of the charge transfer mechanism to the magnetoelectric process in TbMnO3 under magnetic field.